Influence Of Wastewater On Zooplankton Community Of The Daugava River After Daugavpils Wastewater Treatment Plant Modernization (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
During seasonal studies 2010 (May-October, once/ thrice a month), samples of zooplankton were collected at the Daugava River section from 10 km upstream to 10 km downstream from the Daugavpils treatment plant wastewater discharge into the Daugava River. Changes in the quantitative and qualitative characteristics, saprobity index and species diversity (Shannon-Wiener index) were employed for the analysis of zooplankton community structure in the Daugava River. The Daugava River is polluted by Daugavpils wastewater, however the untoward influence of pollution on zooplankton is observed only in years and in seasons with low water level and discharge. The effect of Daugavpils wastewater pollution on changes in the zooplankton community is considered.